ANSWER:
true
STEP-BY-STEP EXPLANATION:
The average is 2. To find the average you add all the numbers then divide the sum by the total amount of numbers.
Answer:
k(4) = 10
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
k(x) = 18 - 2x
k(4) is x = 4
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em>: k(4) = 18 - 2(4)
- Multiply: k(4) = 18 - 8
- Subtract: k(4) = 10
Answer:
![Fx=\frac{5\pm\sqrt{25+24} }{6}](https://tex.z-dn.net/?f=Fx%3D%5Cfrac%7B5%5Cpm%5Csqrt%7B25%2B24%7D%20%7D%7B6%7D)
Step-by-step explanation:
A quadratic equation in one variable given by the general expression:
![ax^2+bx+c](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc)
Where:
![a\neq 0](https://tex.z-dn.net/?f=a%5Cneq%200)
The roots of this equation can be found using the quadratic formula, which is given by:
![x=\frac{-b\pm\sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
So:
![y(x)=3x^2-5x-2=0](https://tex.z-dn.net/?f=y%28x%29%3D3x%5E2-5x-2%3D0)
As you can see, in this case:
![a=3\\b=-5\\c=-2](https://tex.z-dn.net/?f=a%3D3%5C%5Cb%3D-5%5C%5Cc%3D-2)
Using the quadratic formula:
![x=\frac{-b\pm\sqrt{b^2-4ac} }{2a}=\frac{-(-5)\pm\sqrt{(-5)^2-4(3)(-2)} }{2(3)}=\frac{5\pm\sqrt{25+24} }{6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D%3D%5Cfrac%7B-%28-5%29%5Cpm%5Csqrt%7B%28-5%29%5E2-4%283%29%28-2%29%7D%20%7D%7B2%283%29%7D%3D%5Cfrac%7B5%5Cpm%5Csqrt%7B25%2B24%7D%20%7D%7B6%7D)
Therefore, the answer is:
![Fx=\frac{5\pm\sqrt{25+24} }{6}](https://tex.z-dn.net/?f=Fx%3D%5Cfrac%7B5%5Cpm%5Csqrt%7B25%2B24%7D%20%7D%7B6%7D)